Masculine Models in El cautiverio feliz: Medieval Nostalgia in a Degraded Present (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
In this essay, I study how Pineda and Bascuñán use alternative masculinities as a narrative strategy to criticize Chilean colonial institutions, while at the same time trying to benefit from them. In this text, he constructs himself as a victim of the corrupt and outdated policies of a patriarchal state and finds himself a captive that suffers greatly and sees his masculinity reduced due to that victimization. He presents contrasting masculine models, one positive and medieval, based on strength and caring, and the other negative and contemporary, based on cowardice and greed. Ultimately, the text is also an alternative project of nation, conquest, and colonization based on “maternal” qualities such as caring, compassion, and tolerance.